Autonomous Learning Strategies in the Reading Comprehension of High School Students - Medina Coronado, Daniela (2019)
When observing in the high school as well as higher education classrooms, the way adolescents and young people study, the idea of knowing if they have strategies for autonomous learning and if this variable explained to some extent a critical problem in Peru arose: reading comprehension. That is why it was proposed as a purpose of the study, to know if the autonomous learning strategies, its dimensions and indicators have some explanatory power on reading comprehension. Under a causal correlational design of an exploratory nature, the following instruments were applied: Autonomous work strategies questionnaire (CETA) that evaluates the strategies of expansion, collaboration, conceptualization, planning, preparation of exams and participation and PECL 2 test to measure levels of reading comprehension: literal, inferential and evaluative in a group of 144 students from educational institutions from the districts of Majes in Arequipa and Villa Rica in Pasco. Among the most important results was that 79.33% of students reached a level in process regarding the use of autonomous learning strategies and 62.7% reached the same level in reading comprehension. Likewise, it was found that 34.4% of the reading comprehension variable is accounted for the use of autonomous learning strategies. Out of that total, 25.8% for expansion strategies, 14.3% for collaboration strategies, 28.7% for conceptualization strategies, 19.6% for exam preparation strategies and finally, 19.5% for participation strategies.